2008
DOI: 10.1016/j.heares.2008.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Age-related auditory pathology in the CBA/J mouse

Abstract: Commercially obtained aged male CBA/J mice presented a complex pattern of hearing loss and morphological changes. A significant threshold shift in auditory brainstem responses (ABR) occurred at 3 months of age at 4 kHz without apparent loss of hair cells, rising slowly at later ages accompanied by loss of apical hair cells. A delayed high-frequency deficit started at 24 kHz around the age of 12 months. At 20 to 26 months, threshold shifts at 12 and 24 kHz and the accompanying hair cell loss at the base of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
100
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(107 citation statements)
references
References 30 publications
6
100
1
Order By: Relevance
“…ABR and DPOAE findings here are consistent with reports of progressive age-related decreases in both inner and outer hair cell densities (Spongr et al 1997), loss of spiral ganglion fibers (Ohlemiller and Gagnon 2004), and confirm and extend previous studies of age related changes in auditory function reported for the CBA/CaJ mouse strain (Guimaraes et al 2004;Henry 2004;Sha et al 2008).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…ABR and DPOAE findings here are consistent with reports of progressive age-related decreases in both inner and outer hair cell densities (Spongr et al 1997), loss of spiral ganglion fibers (Ohlemiller and Gagnon 2004), and confirm and extend previous studies of age related changes in auditory function reported for the CBA/CaJ mouse strain (Guimaraes et al 2004;Henry 2004;Sha et al 2008).…”
Section: Discussionsupporting
confidence: 91%
“…The EP is inherently difficult to measure and varies by measurement site, species, and genetic strain. For example, in gerbils and BALB/cJ mice, the EP has been shown to decline as a function of age (Gratton et al 1996), whereas the C57BL/6 J and CBA/CaJ mouse strains show no change or limited change in the EP (Lang et al 2002;Ohlemiller et al 2006;Wu and Marcus 2003;Sha et al 2008). The finding that the EP does not decrease with age in the CBA/CaJ strain makes it unlikely that this is the underlying basis for the decreased cochlear sensitivities seen here with aging.…”
Section: Discussionmentioning
confidence: 99%
“…Because the Cdh23 753A mutation is known to promote early onset of AHL in C57BL/6J mice (4-6, 8, 9), it is possible that hair cells in mice carrying the Cdh23 753A mutation are more susceptible to oxidative stress and apoptosis, thereby limiting the general implication of our findings. However, the C57BL/6J strain displays the classic pattern of AHL (4, 5, 7), similar to that reported in humans (1,38) and in the CBA/J mouse strain that does not possess the Cdh23 753A mutation and displays late onset of AHL by 18 months of age (4,7,39). In both strains, the onset of AHL begins in the high-frequency region and spreads toward the low frequencies with age, and the loss of hair cells and neurons begins in the base and spreads toward the apex of the cochlea with age (4,5,7,39).…”
Section: Discussionsupporting
confidence: 80%
“…7,8 This is similar to presbyacusis, that affects higher frequencies first. 9,10 Sensory hair cell loss and cochlea neuron loss at the basal turns are thought to be responsible for presbyacusis. 11 Nakae et al made similar observations in an animal model of diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%